"A Hideous and a Wicked Country": Cornwall under the Travel Writer's Gaze, and Receiving Travelers' Texts as a "Travelee-Reader". (4th May 2019) - Hannigan, Tim
Abstract : This article focuses on travel accounts about Cornwall from "the long nineteenth century, " including those by Wilkie Collins and W.H. Hudson. The article traces a shift from a general hostility to "deformed" Cornish topography to an almost universal celebration of its "rugged beauty, " coupled with a consistent tendency to exoticize local culture, and considers the changing impetus of this othering—from an integrationist ideology at the outset, to a desire to maintain an exotic "elsewhere" as counterpoint to the metropolis later on. The second part of the article takes a self-reflexive approach, drawing on my own background as a self-identifying Cornish person to consider how such outsider representations might interact with local auto-exoticizing discourses. Drawing on Wendy Bracewell's work on "travelee polemics" and the "travelee reader, " the article argues that receiving exoticizing travel texts may have a validating quality in a community that self-identifies as "different" from a national mainstream.